Análise da rentabilidade de centrais de geração hidrelétricas em instalações residenciais - Gianani, Anjli Hero (2023)
The Small Hydroelectric Power Plants (PCHs) of Distributed Micro and Mini-generation (MMGD) present a promising solution for the diversification of the Brazilian energy matrix. Specifically, the idea of the project is based on the installation of turbines with generators in the building’s water distribution system, allowing the decentralized generation of hydroelectric energy. This approach takes advantage of the water flow already present in the pipes, reducing losses and maximizing the use of available energy potential. The installation of turbines with generators takes advantage of an existing resource, without the need to build dams or other significant environmental impacts. This contributes to the diversification of the energy matrix, reducing dependence on non-renewable sources and promoting the transition to a low-carbon economy. In addition to the environmental benefits, the project also has economic advantages. Decentralized energy generation allows buildings to produce part of the energy they consume, reducing dependence on large power plants and increasing the resilience of the electrical system. Although it is important to carry out detailed studies to assess the technical and economic viability of each project, the idea of SHPs in MMGD demonstrates the potential to attract investors interested in taking advantage of the financial and environmental benefits of this innovative approach. The analysis of the surrounding equation allowed the development of a spreadsheet using spreadsheet software. This worksheet makes it possible to speed up project prospecting. The results obtained by its use, when compared to other studies, show an average difference of 70%. This value is due to the fact that the compared methods, despite having the same objective, are not identical and take into account other calculation constraints. Even só, the validations were important, proving to be palpable and demonstrating the energetic potential of the Building.